1994
DOI: 10.3109/10915819409140991
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Crataegus (Hawthorn) Extract (WS 1442)

Abstract: An extract of Crataegus-WS 1442-standardized by a special process of production and adjusted to 18.75% oligomeric procyanidines, was investigated in single and repeat-dose toxicity studies. No target organ toxicity was defined at high multiples of the human dose (100 times) and the battery of standard mutagenic and clastogenic tests were negative. The results presented are for Crataegus extract WS 1442 only; other preparations of Crataegus have to be investigated case by case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…56 In the same context, experiments in rats and mice showed that the hydroalcoholic extract of leaves and flowers can be administered up to 3000 mg/kg without any mortality or abnormal symptoms. 57 It was also demonstrated that CABAE administration significantly and dose-dependently protected against castor oil-induced hypersecretion by inhibiting all studied diarrhea parameters (frequency and severity of diarrhea, onset of the first defecation, number of wet and total number of stools). Castor oil-induced intestinal hypersecretionis a well-known model of acute diarrhea 9 acts via its main compound, ricinoleic acid.…”
Section: Discussionmentioning
confidence: 85%
“…56 In the same context, experiments in rats and mice showed that the hydroalcoholic extract of leaves and flowers can be administered up to 3000 mg/kg without any mortality or abnormal symptoms. 57 It was also demonstrated that CABAE administration significantly and dose-dependently protected against castor oil-induced hypersecretion by inhibiting all studied diarrhea parameters (frequency and severity of diarrhea, onset of the first defecation, number of wet and total number of stools). Castor oil-induced intestinal hypersecretionis a well-known model of acute diarrhea 9 acts via its main compound, ricinoleic acid.…”
Section: Discussionmentioning
confidence: 85%
“…But Trials have evaluated dosages ranging from 160 to 1800 mg/day standardized extracts in divided doses over 2 to 24 weeks (Schlegelmilch and Heywood, 1994). Minimum effective doses are suggested to be standardized extract 100 (Shatoor, 2011) and 300 mg (Schlegelmilch and Heywood, 1994) daily. Crataegus is reportedly toxic in high doses; low doses of Crataegus usually lack adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Like the other lymphatic organs, it gives rise to lymphocytes that pass into the circulating blood. Because of its location in the bloodstream, the spleen responds very quickly to the antigens that invade the blood, being a phagocytic and immunological filter, as well as a large producer of antibodies [23,33].…”
Section: Discussionmentioning
confidence: 99%